High frequency of MYC gene amplification is a common feature of radiation-induced sarcomas. Further results from EORTC STBSG TL 01/01 - Käcker, Christoph; Marx, Alexander; Mößinger, Katharina; Svehla, Frederike; Küffer, Stefan; Sauer, Christian; Hohenberger, Peter; Ströbel, Philipp (Genes, chromosomes & cancer, 2013)
Irradiation is a major causative factor among the small subgroup of sarcomas with a known etiology. The prognosis of radiation-induced sarcomas (RIS) is significantly worse than that of their spontaneous counterparts. The most frequent histological subtypes include undifferentiated pleomorphic sarcomas, angiosarcomas, and leiomyosarcomas. A high frequency of MYC amplifications in radiation-induced angiosarcomas, but not in primary angiosarcomas, has recently been described. To investigate whether MYC amplifications are also frequent in RIS other than angiosarcomas, we analyzed the MYC amplification status of 83 RIS and 192 sporadic sarcomas by fluorescence in situ hybridization. We found significantly higher numbers of MYC amplifications in RIS than in sporadic sarcomas (P < 0.0001), especially in angiosarcomas, undifferentiated pleomorphic sarcomas, and leiomyosarcomas. Angiosarcomas were special in that MYC amplifications were particularly frequent and always high level, while other RIS showed low-level amplifications. We conclude that MYC amplifications are a frequent feature of RIS as a group and may contribute to the biology of these tumors. © 2012 Wiley Periodicals, Inc.